THE ROLE OF GOAL SETTING IN METACOGNITIVE AWARENESS AS A SELF-REGULATORY BEHAVIOR IN FOREIGN LANGUAGE LEARNING - Nihan Bursalı; Huseyin Oz (International Online Journal of Education and Teaching, 2018)
Metacognition, an awareness of one’s own cognitive processes in learning, is a crucial component of self-regulatory behavior that facilitates successful language learning. Therefore, the current study sought to find out the role of different types of goals in participants’ metacognitive awareness. A total of 118 university students enrolled in an English Language Teaching program at a major state university voluntarily participated in the study. Data were gathered using Metacognitive Awareness Inventory (MAI) and Goals Inventory. Findings of descriptive statistics revealed that 48.3% of the participants had high, 28% had moderate, and 23.7% had low metacognitive awareness. Besides, significant correlation was found between mastery goals and metacognitive awareness, supporting the findings of the previous studies. These results revealed the importance of goal setting in metacognition and can be useful for practitioners to include goal orientation to the curriculum by emphasizing the necessity of learner engagement, agency, and self-regulation for successful language learning process.